2011
DOI: 10.1007/s10548-011-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Plasticity in 4-Month-Old Infants: Specific Effects of Experience with Musical Timbres

Abstract: Animal models suggest that the brain is particularly neuroplastic early in development, but previous studies have not systematically controlled the auditory environment in human infants and observed the effects on auditory cortical representations. We exposed 4-month-old infants to melodies in either guitar or marimba timbre (infants were randomly assigned to exposure group) for a total of ~160 min over the course of a week, after which we measured electroencephalogram (EEG) responses to guitar and marimba ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 80 publications
3
34
0
Order By: Relevance
“…Recent longitudinal studies have observed structural (Hyde et al, 2009) and functional (Seither-Preisler, Parncutt, & Schneider, 2014; Trainor, Lee, & Bosnyak, 2011) music-induced neuroplasticity that corroborates correlational differences between adult musicians and nonmusicians (for reviews, see Herholz & Zatorre, 2012; Münte, Altenmüller, & Jäncke, 2002). Multiple studies have suggested that the neural basis of the reported music-to-other-cognition transfer effects involves enhancement of neural resources shared with general executive cognition; however, they acknowledge that the methods failed to capture sufficient cortical dynamics to describe a more specific mechanism (Moreno et al, 2011; Jentschke & Koelsch, 2009; Patel, 2003).…”
Section: Introductionmentioning
confidence: 60%
“…Recent longitudinal studies have observed structural (Hyde et al, 2009) and functional (Seither-Preisler, Parncutt, & Schneider, 2014; Trainor, Lee, & Bosnyak, 2011) music-induced neuroplasticity that corroborates correlational differences between adult musicians and nonmusicians (for reviews, see Herholz & Zatorre, 2012; Münte, Altenmüller, & Jäncke, 2002). Multiple studies have suggested that the neural basis of the reported music-to-other-cognition transfer effects involves enhancement of neural resources shared with general executive cognition; however, they acknowledge that the methods failed to capture sufficient cortical dynamics to describe a more specific mechanism (Moreno et al, 2011; Jentschke & Koelsch, 2009; Patel, 2003).…”
Section: Introductionmentioning
confidence: 60%
“…After half of these children underwent one year of piano training, however, these same children showed strengthened induced gamma-band activity in response to piano tones (Trainor et al, 2009). In fact, it was subsequently observed that infants simply exposed to music for ~160 min over the course of a week to a particular musical timbre demonstrate enhanced timbre-specific cortical responses (Trainor et al, 2011), supporting the interpretation that little instrumental exposure is necessary to induce cortical timbre specializations. To determine whether the expression of timbre-specific encoding within the auditory brainstem unfolds with similar rapidity, we collected cABRs to piano, bassoon and tuba tones in children who had undergone instrumental training for anywhere from 3 to 10 years, predicting that children would demonstrate preferential cABRs to their own instrument.…”
Section: Experience-related Contributions To the Musician's Auditory mentioning
confidence: 92%
“…The mother could choose between a classical piece, a short Latin American melody, or a children's melody. Although some musical genres may be more facilitative than others (46), unfortunately, the music choices were not recorded.…”
Section: Methodsmentioning
confidence: 99%